Rives S. Brown scrapbooks - Brown, Rives S.
Four volumes containing selections of materials, ration books, telegrams, directives, and orders of the Office of Price Administration.
Collection material in English.
Keywords: United States. -- Office of Price Administration; Rent control; World War, 1939-1945 -- Economic aspects -- United States